Alternative paradigms the impact of Islamic and Western Weltanschauungs on political theory - Davutoglu, Ahmet (University Press of America, 1994)
Offers a comparative analysis between Western and Islamic political theories and images. Davutoglu argues that conflicts between these two ideals originate from their philosophical, methodological, and theoretical background rather than only institutional and historical differences.